SELF-EFFICACY AND SOCIAL LOAFING BEHAVIOR AMONG MEMBERS OF EDUCATIONAL COMMUNITIES IN KUPANG CITY - Ester Melani Jeni Ratu; Mernon Yerlinda Carlista Mage; Theodora Takalapeta (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The phenomenon of social loafing, or the tendency to reduce individual contributions to group assignments, poses a real challenge to the effectiveness of non-formal educational communities. This study aims to analyze the relationship between self-efficacy and social loafing behavior among members of educational communities in Kupang City. Using a quantitative approach with a correlational design, the study involved 148 active participants from 17 educational communities selected through incidental sampling. Data were collected using an online questionnaire that included the Self-Efficacy Scale and the Social Loafing Scale, and then analyzed using the Spearman's rho statistical test. The findings showed a significant correlation between the two variables, with the majority of respondents at moderate levels for both aspects. Data analysis indicates that self-efficacy serves as a crucial internal factor; individuals with high self-efficacy tend to have greater engagement and lower levels of social loafing. In addition to psychological factors, external dynamics such as clear role allocation and supportive leadership also influence member participation. It is concluded that strengthening self-efficacy through structured community activities and providing feedback is essential to minimize passive behavior and increase collective organizational productivity. ABSTRAK Fenomena social loafing atau kecenderungan mengurangi kontribusi individu dalam tugas kelompok menjadi tantangan nyata bagi efektivitas komunitas pendidikan nonformal. Penelitian ini bertujuan untuk menganalisis hubungan antara self-efficacy dan perilaku social loafing pada anggota komunitas pendidikan di Kota Kupang. Menggunakan pendekatan kuantitatif dengan desain korelasional, studi ini melibatkan 148 partisipan aktif dari 17 komunitas pendidikan yang dipilih melalui teknik incidental sampling. Pengumpulan data dilakukan menggunakan kuesioner daring yang mencakup Skala Self-Efficacy dan Skala Social Loafing, kemudian dianalisis menggunakan uji statistik Spearman’s rho. Temuan penelitian menunjukkan adanya korelasi yang signifikan antara kedua variabel, di mana mayoritas responden berada pada tingkat sedang untuk kedua aspek tersebut. Analisis data mengindikasikan bahwa self-efficacy berfungsi sebagai faktor internal krusial; individu dengan keyakinan diri yang tinggi cenderung memiliki keterlibatan yang lebih besar dan tingkat social loafing yang lebih rendah. Selain faktor psikologis, dinamika eksternal seperti kejelasan pembagian peran dan kepemimpinan yang suportif turut memengaruhi partisipasi anggota. Disimpulkan bahwa penguatan self-efficacy melalui aktivitas komunitas yang terstruktur dan pemberian umpan balik sangat diperlukan untuk meminimalkan perilaku pasif serta meningkatkan produktivitas kolektif organisasi.